Pengaruh Pengawasan dan Kompetensi Kepegawaian Terhadap Efektivitas Pemungutan Retribusi Parkir Oleh UPTD (Unit Pelaksana Teknis Dinas) LLAP (Lalu Lintas Angkutan dan Parkir) di Kecamatan Kota Bekasi Timur - Nabila Dwi Maharani; Wahidin Septa Zahran; Vita Vitisia (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Human resources are the most important factor in supporting the success of a company. Regional Original Income (PAD) is income that shows the ability of a region to collect sources of funds to finance regional activities. Supervision is basically fully directed to avoid any possibility of deviation from the objectives to be achieved.This study aims to find out and analyze how much the relationship between supervision and staffing competence has on the effectiveness of parking retribution collection by the UPTD (Service Technical Implementation Unit) LLAP (Transportation and Parking Traffic) of the Department of Transportation in East Bekasi District. The sample in this study were 60 LLAP Employees of the Department of Transportation, East Bekasi City District and the Community. The method used in this research is a quantitative descriptive method. The results of the study show that supervision of 62.2% has an effect on the Effectiveness of Parking Retribution Collection. And the t-test shows that there is a positive and significant effect. Personnel Competence of 43.9% has an effect on the Effectiveness of Parking Retribution Collection and the t-test shows that there is a positive and significant influence. Simultaneous test results show that Supervision and Personnel Competence have an effect of 65.8% on the Effectiveness of Parking Retribution Collection. Based on the Anova F Test, it is known that the value of Sig. is equal tob 0.001 <0.05, it can be concluded that Supervision (X1) and Personnel Competence (X2) simultaneously affect the Effectiveness of Parking Retribution Collection (Y)